2022
DOI: 10.1021/acsami.2c01137
|View full text |Cite
|
Sign up to set email alerts
|

Wearable Sensors Adapted to Extreme Environments Based on the Robust Ionogel Electrolytes with Dual Hydrogen Networks

Abstract: Nonvolatile ionogels are promising soft electrolyte materials for flexible electronics, but it is challenging to fabricate stable electrolytes with mechanical robustness. Here, through rationally optimizing the chemical structure of polymer matrix and ionic liquids, the high-performance ionogel electrolytes with mechanical robustness and stability were fabricated. There are double hydrogen bonding networks in the as-prepared ionogel electrolytes, one of which exists between the polymer chains while the other o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 40 publications
0
31
0
Order By: Relevance
“…The TCR is defined as follows: TCR = (Δ R / R 0 )/Δ T , where Δ T represents the change in temperature. 57 As shown in Fig. 4(c), the TCR also decreased with the increase of temperature.…”
Section: Resultsmentioning
confidence: 62%
“…The TCR is defined as follows: TCR = (Δ R / R 0 )/Δ T , where Δ T represents the change in temperature. 57 As shown in Fig. 4(c), the TCR also decreased with the increase of temperature.…”
Section: Resultsmentioning
confidence: 62%
“…Further, numerous studies have reported the virtue of synthetic variation of monomer-based IL-SICs. 89,90,[93][94][95][96][97][98][99][102][103][104][105][106][107][108][109] Recently, Sun et al reported a triboresistive touch sensor based on the ionic PDMS. 91 The ionic PDMS in that study was composed of hydrophilic PDMS and hydrophobic IL through H-bonding and van der Waals interactions (Fig.…”
Section: Il-based Sics (Il-sics)mentioning
confidence: 99%
“…To combine polymers with ILs, it is important to find appropriate interactions between the functional groups of polymers and ILs, as these interactions determine their compatibility. The polymers can be roughly classified as polymer-based type 52,74–88 and monomer-based type, 89–109 and the ILs are composed of diverse pairs of the cationic and the anionic units (Fig. 7a and b).…”
Section: Stretchable Ionic Conductors (Sics)mentioning
confidence: 99%
See 1 more Smart Citation
“…The designable composition and structure of ILs/polymer network as well as the synergistic effect between ILs and polymer matrix enable ionogels to integrate more favorable features. [ 29,30 ] As expected, significant research efforts have been devoted to the molecular design to achieve high‐performance ionogels. Well‐defined ionogels with highly effective energy dissipation networks, such as hybrid networks, nanocomposites networks, and double‐networks (DN structure), have been specially designed and fabricated.…”
Section: Introductionmentioning
confidence: 98%